In Vitro Inhibition of Human CYP450s 1A2, 2C9, 3A4/5, 2D6 and 2E1 by Grandisin - Habenschus, Maísa Daniela; Moreira, Fernanda de Lima; Lopes, Norberto Peporine; de Oliveira, Anderson R. M. (Planta Medica, 2017)
Grandisin, a lignan isolated from many species of plants, such as Virola surinamensis, is a potential drug candidate due to its biological properties, highlighted by its antitumor and trypanocidal activities. In this study, the inhibitory effects of grandisin on the activities of human cytochrome P450 enzymes were investigated by using human liver microsomes. Results showed that grandisin is a competitive inhibitor of CYP2C9 and a competitive and mechanism-based inhibitor of CYP3A4/5. The apparent Ki value for CYP2C9 was 50.60 µM and those for CYP3A4/5 were 48.71 µM and 31.25 µM using two different probe substrates, nifedipine and midazolam, respectively. The apparent KI, kinact, and kinact/KI ratio for the mechanism-based inhibition of CYP3A4/5 were 6.40 µM, 0.037 min−1, and 5.78 mL · min−1 µmol−1, respectively, by examining nifedipine oxidation, and 31.53 µM, 0.049 min−1, and 1.55 mL · min−1 µmol−1, respectively, by examining midazolam 1′-hydroxylation. These apparent kinact/KI values were comparable to or even higher than those for several therapeutic drugs that act as mechanism-based inhibitors of CYP3A4/5. CYP1A2 and CYP2D6 activities, in turn, were not substantially inhibited by grandisin (IC50 > 200 µM and 100 µM, respectively). In contrast, from a concentration of 4 µM, grandisin significantly stimulated CYP2E1 activity. These results improve the prediction of grandisin-drug interactions, suggesting that the risk of interactions with drugs metabolized by CYP3A4/5 and CYP2E1 cannot be overlooked.
Keywords: cytochrome p450 inhibition; grandisin; drug interactions; human liver microsomes; mechanism-based inhibition